How animal and plant-based proteins affect energy metabolism during the postprandial phase in overweight and obese men: a cross-over design study - Zahra Dehnavi; Shima Sabbaghi; Ali Jafarzadeh Esfehani; Mahnaz Namazi; Fahimeh Hoseinzadeh; Hanieh Barghchi; Monireh Dahri; Reza Rezvani; Mahdi Shadnoush; Mohammad Safarian (Nutrition Journal)
Abstract Background Animal proteins (APs) and plant proteins (PPs) seem to exhibit different thermic and metabolic effects, which may be attributed to differences in amino acid profiles, bioavailability, and digestibility. Objectives In this study, we aimed to investigate and compare the postprandial effects of AP and PP meals on energy metabolism parameters, including resting energy expenditure (REE) and substrate oxidation (SO), in overweight and obese men. Methods This acute randomized crossover clinical trial involved forty-eight overweight and obese men, with a mean age of 33.48 ± 8.35 years and an average BMI of 29.15 ± 2.33 kg/m2. Participants consumed two high-protein test meals with different protein sources (AP and PP) on separate days, with a washout period of 7 to 10 days between them. On each test day, energy metabolism parameters were measured in both the fasting state and postprandial phase using indirect calorimetry. Statistical analysis was conducted using SPSS version 25 and R programs, evaluating the effects of carry-over, treatment, time, and treatment × time interaction through generalized estimating equations (GEE) analysis. Results After controlling for baseline values, there was a significant effect of time (P < 0.05), protein source (P < 0.05), and protein source × time (P < 0.05) on REE, TEF, and carbohydrate oxidation. REE showed an increase following the consumption of both meals; however, the rise observed after AP (14.2%) was greater than that of PP (9.55%). The trends in TEF changes were similar to those of REE. The mean carbohydrate oxidation after consuming PP remained relatively stable throughout the test, whereas the AP meal gradually increased, reaching its peak at the 180th minute. The decline in carbohydrate oxidation was more pronounced following the AP meal than the PP meal by the end of the test. Conclusion This clinical trial demonstrates that animal-based protein results in higher energy expenditure and carbohydrate oxidation than plant-based protein.